2020
DOI: 10.1021/acs.cgd.0c00370
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelastic Domains in a CsPbBr3 Single Crystal and Their Phase Transition Characteristics: An in Situ TEM Study

Abstract: The all-inorganic halide perovskite CsPbBr3 has attracted significant attention for applications of high-performance and stable solar cells, light-emitting diodes (LEDs), and photoelectric and X-/γ-ray detectors. The discrepant photoelectric properties are confusing, which strongly implies that the perovskite is sensitive to defects. Here, novel and ubiquitous defects, “twin domains”, are reported in solution-grown CsPbBr3 single crystals on the basis of X-ray diffraction techniques, optical microscopy, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
7
25
0
Order By: Relevance
“…29−32 Likewise, ferroelastic domains could be formed in CsPbBr 3 single crystals induced by phase transitions. 33 Ferroelectric materials additionally exhibit electric polarization, which could affect the performance of MHP solar cells. 34−37 Studying ferroelectricity and ferroelasticity in MHPs is therefore important, both for applications and for a fundamental understanding of these materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…29−32 Likewise, ferroelastic domains could be formed in CsPbBr 3 single crystals induced by phase transitions. 33 Ferroelectric materials additionally exhibit electric polarization, which could affect the performance of MHP solar cells. 34−37 Studying ferroelectricity and ferroelasticity in MHPs is therefore important, both for applications and for a fundamental understanding of these materials.…”
mentioning
confidence: 99%
“…In ferroelastic materials, stress leads to the formation of domains with different crystal orientation . It has been demonstrated that ferroelasticity can be a key to induce domain formation in different structures, including epitaxial tetragonal phase perovskites. , If two interfacing domains have different lattice spacings, the domains will generally tilt due to the lattice mismatch at the domain walls. Likewise, ferroelastic domains could be formed in CsPbBr 3 single crystals induced by phase transitions . Ferroelectric materials additionally exhibit electric polarization, which could affect the performance of MHP solar cells. Studying ferroelectricity and ferroelasticity in MHPs is therefore important, both for applications and for a fundamental understanding of these materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the study of phase transitions in CsPbBr 3 , several methods, such as selected area electron diffraction (SAED), 74 neutron diffraction, 75 hightemperature X-ray diffraction, 76,77 and DSC, [76][77][78] have been used. Zhang et al 74 studied phase transition in single-crystal CsPbBr 3 (synthesized using inverse temperature crystallization method) using the SAED patterns monitored through transmission electron microscopy (TEM) at various temperatures. The SAED patterns at different temperatures are shown in Fig.…”
Section: 21mentioning
confidence: 99%
“…Selecting an all-inorganic counterpart with controllable ferroic domains would help study their function on optoelectronic properties. A CsPbBr 3 single crystal is a promising candidate for γ-ray detection, within which the existence of {121} reflection and 90° rotation ferroelastic twin domains has been demonstrated . Building the correlation between ferroelastic domains and optoelectronic properties in CsPbBr 3 should be a non-trivial task for understanding the mechanism behind the domain-adjusted optoelectronic properties.…”
mentioning
confidence: 99%